2018
DOI: 10.1590/1678-4685-gmb-2016-0162
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous sequence variants in the WNT10B gene underlie split hand/foot malformation

Abstract: Split-hand/split-foot malformation (SHFM), also known as ectrodactyly is a rare genetic disorder. It is a clinically and genetically heterogeneous group of limb malformations characterized by absence/hypoplasia and/or median cleft of hands and/or feet. To date, seven genes underlying SHFM have been identified. This study described four consanguineous families (A-D) segregating SHFM in an autosomal recessive manner. Linkage in the families was established to chromosome 12p11.1–q13.13 harboring WNT10B gene. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…uruguayus , whereas it is submetacentric and significantly smaller in species of the S . catharinae clade (e.g., [103,170–179]). Cardozo et al [103] suggested that the submetacentric Pair 1 constitutes a synapomorphy of the S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uruguayus , whereas it is submetacentric and significantly smaller in species of the S . catharinae clade (e.g., [103,170–179]). Cardozo et al [103] suggested that the submetacentric Pair 1 constitutes a synapomorphy of the S .…”
Section: Discussionmentioning
confidence: 99%
“…uruguayus , and most other species of the S . ruber clade have NORs on Pair 11 (e.g., [103,172175,179]), like many other Hylines with 2 n = 24 (see [177,178], and cites therein). The exceptions are S .…”
Section: Discussionmentioning
confidence: 99%
“…A number of families has been reported previously from Pakistan having different mutations in the WNT10B leading to SHFM phenotypes (22)(23)(24). Khan et al (9), Aziz et al (24), and Ullah et al (25), studied several Pakistani consanguineous SHFM families using linkage analysis followed by direct sequencing and identified pathogenic variants in the WNT10B gene (9,24,25). The Clinical features of affected members in these families exhibited SHFM phenotype, which is inherited in the form of autosomal recessive pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Other WNT genes such as WNT3, WNT4, WNT6, WNT7A, WNT7B, WNT9B, WNT10A, and WNT16 as well as WNT10B show higher expression throughout the limb bud ectoderm in all phases of mouse limb formation with the exception of the apical ectodermal ridge where Wnt10b expression is only seen at embryonic day 11.5 (E11.5) (29,30). A few individuals were described carrying WNT10B variants exhibiting developmental tooth alterations, low bone mass or obesity but causality was not established (25,26,31,32). Such phenotypes were not observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is categorized into two types: the postaxial type A (PAPA; well-developed extra digit) and the postaxial type B (PAPB; hypoplastic rudimentary extra digit or a skin tag or appears as a small protuberance). Polydactyly may occur as a non syndromic form (isolated) or in association with other severe abnormalities (syndromic form) such as Bardet-Biedl syn drome, split hand/foot malformation, syndactyly, and Ellis-Van Creveld syndrome, respectively (Khan et al, 2012;Ullah, Gul, et al, 2018;Ullah, Khalid, et al, 2018;Ullah, Umair, et al, 2017Umair, Ahmad, Bilal, & Abbas, 2018Umair, Ahmad, Bilal, Ahmad, & Alfadhel, 2018;Umair, Seidel, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%